Descriptions of two new species of leafhopper genus Uniformus (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) from China - Song, Yuanyuan; Huang, Min (Zootaxa, 2023)
Two new species, U. robustispinus Song & Huang and U. semicircularis Song & Huang spp. nov., of the leafhopper genus Uniformus Jiao & Yang, 2020 from China are described and illustrated. A key to species and a checklist of Uniformus are provided.